Imaging Findings in Neurogenic Ptosis - Yiseul Son; Eun Ja Lee; Nam-Hee Kim; So Jeong Lee (Journal of the Korean Society of Radiology)
Neurogenic ptosis refers to upper eyelid drooping resulting from disrupted innervation of the eyelid retractor muscles. The differential diagnoses of neurogenic ptosis include oculomotor nerve palsy, Horner’s syndrome, and neuromuscular junction disorders. Oculomotor nerve palsy and Horner’s syndrome result from damage to the oculomotor and oculosympathetic pathways, respectively. The oculomotor nerve pathway has four segments: intraaxial, subarachnoid, cavernous, and orbital. The oculosympathetic pathway consists of three orders of neurons extending from the base of the skull to the upper chest. Several pathologic conditions can affect these neural pathways and cause neurogenic ptosis owing to the long course of the involved nerves. Therefore, neurogenic ptosis is usually associated with unique clinical features based on the anatomical location of the pathology. This pictorial essay provides a deeper understanding of the neural pathways and different diseases that cause neurogenic ptosis, which can help in determining the location of the pathology.